INOVASI MARKETING COMMUNICATION PRODUK GRAMEEN BANK UNTUK PEMBERDAYAAN KOMUNITAS WIRAUSAHA PEREMPUAN - Nada Arina Romli; Dini Safitri; Prima Yustisia; Khairunnisa Rosdiani (Metacommunication: Journal of Communication Studies, 2021)
This study examines the case of the money marketing communication used by Islamic banks to promote Grameen Bank products. Grameen Bank is a form of financing model for providing capital by a bank to a group of people who have a lack of ability in terms of economics. This study aims to determine the marketing mix model used by BTPN Syariah in attracting the interest of the underprivileged community, especially for women to join the PMD program. This is achieved through qualitative research methods with a case study approach. In searching for data, the researcher conducted semi-structured interviews and passive participant observation. The sampling used in this research is snowball sampling. This study uses the basic theory of Symbolic Interaction proposed by George Herbert Mead. This research was conducted on women entrepreneur communities in Jatisampurna and Bantar Gebang. The results of this study are the concept of the marketing mix used, including events and experiences, namely by holding exhibitions and roadshows, world of mouth marketing, using opinion leaders and group meetings, sales promotion girls with sales promotions placed to foster business groups, and by installing advertisements both with print catalog ads (print out advertising) as well as advertisements with digital platforms on YouTube. The marketing strategy used focuses on offline, this is because the target market of Grameen Bank has not yet touched the digital platform.